Anterior shoulder dislocation reduction managed either with midazolam or propofol in combination with fentanyl - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2014)
Objective: Procedural Sedation and Analgesia is used in managing emergency painful procedures. The aim of this study is to compare the effects of propofol and midazolam on haemodynamic parameters when used in combination with fentanyl in isolated anterior shoulder dislocations and to measure the patient and physician satisfactions. Methods: The study is a randomised single blind prospective trial. All procedural sedations were performed by emergency medicine specialists and the shoulder reductions were performed by orthopaedic surgeons. Two groups were defined. Group A received intravenous fentanyl and midazolam and Group B received intravenous fentanyl and propofol. The orthopaedic surgeons were not informed about the drugs. The emergency medicine specialist observed the patients. The patients and the orthopaedic surgeons were asked for a satisfaction scoring. Results: Midazolam group consisted of 37 patients and propofol group consisted of 38 patients. Both groups were similar in demographic characteristics and pre-procedural vital signs. There was only one statistically significant difference at one time and it was the 5th minutes SpO(2) levels between groups. There were statistically significant changes in the measurements of vital parameters in both groups when compared with the baseline levels. However none of them was clinically important. In midazolam and propofol group, 10.8% and 10.5% respectively had respiratory compromise. Patient and physician satisfactions were similar in both groups. Conclusions: Midazolam and propofol are both relatively safe drugs using in combination with fentanyl in anterior shoulder dislocations. Patients and physicians can be highly satisfied with the two groups of drugs.
Keywords: Conscious sedation; drug therapy; emergency medical service; randomized controlled trial; single-blind method; DOUBLE-BLIND TRIAL; EMERGENCY-DEPARTMENT; PROCEDURAL SEDATION; INTRAARTICULAR LIDOCAINE; INTRAVENOUS SEDATION; RECOVERY SCORE; ANALGESIA; ARTHRITIS; INJECTION; KETOFOL